1999
DOI: 10.1038/sj.bjc.6690419
|View full text |Cite
|
Sign up to set email alerts
|

Boswellic acids and malignant glioma: induction of apoptosis but no modulation of drug sensitivity

Abstract: Steroids are essential for the control of oedema in human malignant glioma patients but may interfere with the efficacy of chemotherapy. Boswellic acids are phytotherapeutic anti-inflammatory agents that may be alternative drugs to corticosteroids in the treatment of cerebral oedema. Here, we report that boswellic acids are cytotoxic to malignant glioma cells at low micromolar concentrations. In-situ DNA end labelling and electron microscopy reveal that boswellic acids induce apoptosis. Boswellic acid-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(91 citation statements)
references
References 21 publications
3
88
0
Order By: Relevance
“…Boswellic acids could be the basis for a new kind of anti-inflammatory and thus antiedema medication with decreased adverse effects, the additional induction of apoptosis, and no modulation of drug (and radiation) sensitivity. 19 In addition to the first clinical results, 1,2 our study may be a further step in this direction.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Boswellic acids could be the basis for a new kind of anti-inflammatory and thus antiedema medication with decreased adverse effects, the additional induction of apoptosis, and no modulation of drug (and radiation) sensitivity. 19 In addition to the first clinical results, 1,2 our study may be a further step in this direction.…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, there is evidence that dexamethasone influences cancer therapies through stabilization of blood-brain and blood-tumor barriers and reduction of tumor perfusion. 19 Several years ago, it was shown that the use of steroids influences vascular response to radiation 20 and directly inhibits apoptosis in human malignant glioma cells. 21 However, in spite of strong efforts, an adequate replacement medication for dexamethasone has not been found yet.…”
Section: Discussionmentioning
confidence: 99%
“…However, besides its effect on MM cells, AKBA was also shown to suppress the growth of glioma, colon cancer, prostate and leukemic cells. These effects on multiple cancer targets can occur through the inhibition of the extracellular signal regulated kinase 1 and 2 (ERK1/2) phosphorylation, NF-jB pathway inhibition via IjB kinase (IKK) as well as topoisomerase I inhibition (Glaser et al 1999;Hoernlein et al 1999;Liu et al 2002;Park et al 2002;Shao et al 1998;Syrovets et al 2005 observations suggest that AKBA does not specifically affect STAT3 activity but has a wide field of action. Similarly, the main component isolated from the medicinal plant Nigella sativa, thymoquinone (TQ), was shown to inhibit both constitutive and IL-6-induced STAT3 phosphorylation.…”
Section: Multiple Myelomamentioning
confidence: 99%
“…[1][2][3][4][5] Acetyl-11-keto-β-boswellic acid (AKBA), one of the major active boswellic acids present in boswellia extracts, is a pentacyclic terpenoid, which has been shown to have antitumor effects in different types of tumor cells including colon, 6,7 prostate, 8,9 leukocytes, 10 liver 11 and brain. 12 Several earlier studies have reported inhibitory effects of AKBA on the nuclear factor kappa B (NFκB), 13 and the signal transducer and activator of transcription-3 (STAT-3)-related pathways, 14 which potentiate apoptosis and inhibit angiogenesis in neoplastic cells. However, the precise molecular mechanisms underlying the antitumor effects of AKBA on colorectal cancer (CRC) still remain elusive.…”
Section: Introductionmentioning
confidence: 99%